’O Sole Mio: An Experimental Analysis of Weather and Risk Attitudes in Financial Decisions - Bassi, Anna; Colacito, Riccardo; Fulghieri, Paolo (Review of Financial Studies, 2013)
Although weather has been shown to affect financial markets and financial decision making, a still open question is the channel through which such influence is exerted. By employing a multiple price list method, this paper provides direct experimental evidence that sunshine and good weather promote risk-taking behavior. This effect is present whether relying on objective measures of meteorological conditions or subjective weather assessments. Finally, employing a psychological test, we find evidence that weather may affect individual risk tolerance through its effect on mood.